Pet ownership supports quality of life in home‐dwelling people with Alzheimer's disease. (14th March 2022) - Välimäki, Tarja; Koivisto, Anne; Kärkkäinen, Virve; Selander, Tuomas; Hongisto, Kristiina; Rusanen, Minna
Abstract: Objectives: Human‐animal interactions have beneficial psychosocial and psychophysiological effects on individuals in both the presence and absence of medical health conditions. No previous prospective studies with long follow‐up have investigated the effects of domestic pets on individuals with Alzheimer's disease (AD) who live at home. We examined the effects of pets on quality of life (QoL) and general well‐being during a 5‐year follow‐up of home‐dwelling persons with AD. Methods: In a prospective study including 223 patients with very mild (Clinical Dementia Rating Scale [CDR] 0.5) or mild (CDR 1) AD at baseline who participated in the ALSOVA study, 40 (18%) had a pet. Self‐ and proxy‐rated QoL in AD quality of life‐AD (QoL‐AD), 15D, and self‐rated visual analogic scale (VAS) were assessed annually for 3 years and after 5 years. The Mini‐Mental State Examination, Neuropsychiatric Inventory, and CDR sum of boxes (CDR sum of boxes) were measured at the same visits. Results: A significant positive effect of pet ownership ( p  = 0.003, proxy‐rated QoL‐AD) on QoL was found over the entire follow‐up. However, self‐rated QoL‐AD, 15D, and VAS did not significantly differ between pet owners and non‐pet owners. Conclusions: The findings suggest that having a pet may support QoL in home‐dwelling persons with AD. Self‐rated or general QoL or well‐being measurements are not an accurate method for studying QoL in individuals with dementia over time due to a lack of insight. Adding proxy‐rated evaluations to this kind of study is recommended. Key points: Older adults with Alzheimer's disease living at home with domestic pets preserve their quality of life better than individuals living at home without pets. Having a pet helps older adults with Alzheimer's disease maintain positive relationships and activities of life at home without specific intervention. The disparity with self‐reported and proxy‐reported quality of life scores in the longitudinal study requires further research on the quality of life measurements.